Brasil, um refúgio nos trópicos : a trajetória dos refugiados do nazi-fascismo = Brasilien, Fluchtpunkt in den Tropen - Carneiro, Maria Luiza Tucci (Estação Liberdade, 1996)
"Well-illustrated catalog of exhibition on refugees from Nazi Germany includes documents, letters, and art by exiles"--Handbook of Latin American Studies, v. 58